Understanding burnout and self-regulation capacity in Canadian developmental and elite sport coaches - McNeill, K. (School of Human Kinetics, Faculty of Health Sciences, University of Ottawa, 2018)
The overarching aims of this research were to advance knowledge of coach burnout and interventions addressing this syndrome by investigating (a) the associations between burnout, well-being, self-regulation capacity, and perceived stress in coaches, and (b) the perceived impact of a self-regulation intervention implemented with coaches experiencing moderate to high levels of burnout. A sequential mixed methods design was employed to collect quantitative and qualitative data in two separate phases. In Phase 1, an online survey was used to collect cross-sectional quantitative data from a sample of 260 Canadian developmental and elite sport coaches to assess associations between the variables of interest (i.e., burnout, well-being, self-regulation capacity, and perceived stress). Selected based on data from Phase 1, five coaches experiencing moderate to high levels of burnout then participated in a self-regulation intervention in Phase 2, which involved completing a workbook and a reflective journal and participating in a semi-structured intake and outtake interview before and after the intervention, respectively. Four studies were carried out to address the overall aims of this research. Phase 1. The purposes of Study 1 were to identify profiles of psychological functioning within a sample of coaches based on burnout and well-being indices, and investigate whether coaches in these profiles differed in their capacity to self-regulate and their perceptions of stress. Findings of the two-stage cluster analysis revealed that 54% of the coaches were characterized by a "thriving" profile (i.e., relatively low burnout and relatively high well-being), while 14% of the coaches were characterized by a "depleted" profile (i.e., relatively high burnout and relatively low well-being). The remainder of coaches were characterized by an "at-risk" profile (i.e., relatively high burnout and moderate well-being), which suggests that experiencing symptoms of burnout may not necessarily preclude coaches from experiencing well-being. Moreover, thriving coaches reported higher levels of self-regulation capacity and lower levels of perceived stress than coaches in the two more maladaptive profiles. Depleted coaches also reported higher levels of perceived stress than at-risk coaches. These findings speak to the salience of effective self-regulatory capacity and stress management skills in coaches` adaptive functioning. Finally, depleted coaches worked longer hours and were more likely to be remunerated for their coaching than thriving coaches, demonstrating the importance of monitoring these situational factors to ensure coaches` optimal functioning. The purpose of Study 2 was to examine the associations between self-regulation capacity, perceived stress, and burnout in coaches, and more specifically, to test the intervening variable effect of perceived stress in the association between coaches` self-regulatory capacity and their emotional exhaustion, depersonalization, and personal accomplishment. Results of the structural equation modeling showed that coaches with greater self-regulatory competencies (i.e., self-control and self-observation) perceived less stress in their lives, and in turn, experienced less emotional exhaustion and depersonalization, and greater personal accomplishment (i.e., lower burnout). A direct association between these self-regulatory competencies and coaches` sense of accomplishment was also found. This indicates that effective self-control and self-monitoring competencies may enable coaches to feel more efficacious in their coaching, regardless of their perceptions of stress. Phase 2. The purpose of Study 3 was to investigate coaches` subjective experiences of burnout in order to shed light on the complex emotional nature of this syndrome. To this end, idiographic, first-person narrative accounts of the five coaches` subjective experiences of burnout were provided. The narratives revealed that burnout was highly individualized and characterized by a variety of emotions (e.g., apathy, anger, dejection) linked to the dimensions of burnout. Burnout had negative implications for the coaches` well-being (e.g., loss of enjoyment) and their coaching practice (e.g., yelling at athletes), and was associated with deficits in the coaches` self-regulatory capacity (e.g., resistance to healthy eating and exercise). These findings underscore the need for interventions to help coaches effectively manage their personal and professional life and their symptoms of burnout. The purpose of Study 4 was to implement a self-regulation intervention with coaches experiencing moderate to high levels of burnout and examine the perceived impact of this intervention on their self-regulation capacity and experiences of burnout and well-being. A content analysis of the coaches` outtake interviews and five bi-weekly journals revealed that all five coaches learned to self-regulate more effectively by developing various competencies (e.g., self-monitoring) and strategies (e.g., task delegation) throughout the intervention. Four of the coaches also perceived improvements in their symptoms of burnout (i.e., felt less emotionally drained, more engaged with their work and/or accepting of their athletes, and more effective in their coaching) and their well-being (e.g., experienced more positive emotions, satisfaction with life, and autonomy). Overall, the results of the current research shed light on important personal resources (i.e., self-regulation competencies) that can be strengthened to help coaches prevent or manage burnout and achieve greater well-being. This research also provides data on the first known empirical investigation of an intervention implemented with coaches experiencing burnout. As such, the findings from this dissertation make novel empirical and practical contributions to the literature on coach burnout.